Cluster of Coronavirus disease cluster associated with fitness dance classes, South Korea - Jang, S.; Han, S. H.; Rhee, J.-Y. (Emerging Infectious Diseases Journal, 2020)
During 24 days in Cheonan, South Korea, 112 persons were infected with severe acute respiratory syndrome coronavirus 2 associated with fitness dance classes at 12 sports facilities. Intense physical exercise in densely populated sports facilities could increase risk for infection. Vigorous exercise in confined spaces should be minimized during outbreaks.